2003
DOI: 10.1002/art.11080
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of an activated, profibrotic pattern of gene expression in lung CD8+ T cells from scleroderma patients

Abstract: Objective. Pulmonary fibrosis is a major cause of death in scleroderma patients. Previous studies have shown an increase in CD8؉ T cells in the lungs of scleroderma patients. In the present study, we sought to determine whether activated CD8؉ T cells contribute to pulmonary fibrosis in scleroderma patients through the production and activation of profibrotic mediators.Methods. CD8؉ cells were isolated from bronchoalveolar lavage fluid obtained from 19 scleroderma patients and 7 healthy subjects. The phenotype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
94
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 108 publications
(108 citation statements)
references
References 84 publications
13
94
1
Order By: Relevance
“…By allowing a direct comparison of IFN␥ and IL-4 production potential between T cell subsets generated from healthy and SSc skin, our data highlight the point that CD4ϩCD8ϩ DP as well as CD8ϩ SP T cells, rather than CD4ϩ SP T cells, are the cells producing the high amounts of IL-4. Our results are reminiscent of the finding that the presence of CD8ϩ T cells producing IL-4 in the bronchoalveolar lavage fluid of patients with SSc correlates with development of lung fibrosis (40,41). DP T cells have been observed in patients with various pathologic conditions as well as in normal donors (1).…”
Section: Discussionsupporting
confidence: 69%
“…By allowing a direct comparison of IFN␥ and IL-4 production potential between T cell subsets generated from healthy and SSc skin, our data highlight the point that CD4ϩCD8ϩ DP as well as CD8ϩ SP T cells, rather than CD4ϩ SP T cells, are the cells producing the high amounts of IL-4. Our results are reminiscent of the finding that the presence of CD8ϩ T cells producing IL-4 in the bronchoalveolar lavage fluid of patients with SSc correlates with development of lung fibrosis (40,41). DP T cells have been observed in patients with various pathologic conditions as well as in normal donors (1).…”
Section: Discussionsupporting
confidence: 69%
“…Previous studies have reported that CD8 + T cells infiltrated the skin (6) and lung (7,8) in SSc patients and that CD8 + T cells in lung and peripheral blood showed an activated phenotype (7,9) and Agdriven oligoclonal expansion (8,10,11). These findings indicate that effector or memory CD8 + T cells, or both, are involved in SSc pathogenesis.…”
mentioning
confidence: 68%
“…The disease duration was calculated from the time of onset of the first non-Raynaud phenomenon. Skin sclerosis was evaluated with the modified Rodnan skin thickness score (MRSS) (19) and graded as mild (MRSS, [1][2][3][4][5][6][7][8][9][10][11][12][13][14] or moderateto-severe (MRSS, 15-39) (20). SSc-related interstitial lung disease (ILD) was classified as extensive or limited disease based on combined evaluation with chest high-resolution computed tomography (HRCT) and pulmonary functional tests (21).…”
Section: Patientsmentioning
confidence: 99%
“…CD8ϩ T cells are seen in the pulmonary interstitium on lung biopsy specimens and are increased in the bronchoalveolar lavage fluid from SSc patients with active lung disease (alveolitis) compared with SSc patients with inactive lung disease or no lung disease (11). These T cells exhibit an activated phenotype (HLA-DRϩ), and their presence in the bronchoalveolar lavage fluid is quantitatively associated with progressive and more severe ILD (12,13). Similarly, activated T cells are described in skin biopsy specimens from SSc patients who have early active cutaneous involvement (14).…”
mentioning
confidence: 99%
“…Th2 cytokine expression and secretion are increased in T cells isolated from newly affected SSc skin (21,22). Activated CD8ϩ T cells in bronchoalveolar lavage fluid from SSc patients with alveolitis have higher type 2 cytokine (IL-4 and IL-5) messenger RNA (mRNA) expression (12,13). These data suggest that in SSc, a specific population of activated T cells exhibiting a profibrotic Th2/Tc2-polarized phenotype may be potentially relevant in mediating tissue fibrosis.…”
mentioning
confidence: 99%